Endülüs Nasrî Emiri V. Muhammed El-Ganî-Billâh dönemi (1354-1359)-(1362-1391) - Akyüz, Rumeysa Nurdan (My University, 2019)
İber yarımadasında sekiz asır süren Müslüman hakimiyetinin ilk üç asrı,Müslümanların bölgeyi fethedip burada önemli bir güç olmalarına tanıklık etmiştir.Bu zaman zarfında başarılı hükümdarların iş başına gelmesiyle Endülüs, parlak birdönem yaşamıştır. Ancak XI. yüzyıl itibariyle zuhur eden siyasi parçalanma sonucukuzeydeki Hristiyan krallıkların etkisiyle Müslümanlar Endülüs topraklarını tedricenkaybetmeye başlamışlardır. Bu süreçte bazen Kuzeybatı Afrika’daki Müslümandevletlerin (Muvahhidler, Murâbıtlar, Abdülvâdîler, Merînîler, Hafsîler) yardımlarıylaHristiyan istilaları kısmen yavaşlatılmışsa da netice değişmemiştir.1238 yılında İber yarımadasının güneyinde, Gırnata’da kurulan, Endülüsmedeniyetinin son temsilcileri olan Nasrîler (Benî Ahmer Devleti), kimi zamanKuzeybatı Afrika’daki dindaşlarıyla kimi zaman da İber yarımadasında bulunankomşu Hristiyan krallıklarla sürekli etkileşim halinde bulunmuşlardır. Nasrîlerinkurucusu İbnü’l-Ahmer’den itibaren çalışmamızın konusunu teşkil eden V.Muhammed el-Ganî-Billâh dönemleri arasında başarılı hükümdarların tahtageçmesiyle komşu devletlere karşı başarılı politikalar izlenmiş ve 1391 yılına kadardevlet istikrarlı bir şekilde varlığını sürdürmüştür. Bundan sonraki süreçte başa geçenhükümdarların liyakatsiz oluşu, devleti iyi yönetememesi gibi nedenlerle NasrîDevleti, 1492 yılında Kastilya kraliçesi Elizabeth ile Aragon kralı Ferdinand’ınevlilikleriyle oluşan Hristiyan ittifakına karşı direnç gösterememiş ve Nasrîlerlebirlikte bu coğrafyada siyasi olarak Müslüman varlığı son bulmuştur.

In the first three centuries of Muslim rule in the Iberian peninsula whichremained as such for eight centuries, Muslims conquered a major portion of theIberian peninsula and consolidated their power. During this time, al-Andalus had abright period thanks to the success of the rulers. However, as a result of the politicaldisintegration which had started in XI. century, gradually Muslims gradually startedto lose the Andalusian lands to the Christian kingdoms in the North. Despite the factthat Christian invasions were sometimes slowed down owing to the help of Muslimstates in North Africa (Almohades, Murabites, Abdulvadis, Merinids, Hafsids),Muslims eventually lost their foothold in this region.In 1238 the Nasris (Beni Ahmer State) were established in Girnata in the southof the Iberian peninsula as the last kingdom of the Andalusian civilization. Duringtheir rule, they continuously interacted with both their coreligionists living inNorthwest Africa and neighbouring Christian kingdoms in the Iberian peninsula. Theperiod covered between the first founder of Nasrids, Ibnu Al-Ahmer, and MuhammedV al-Ghani Billah, the subject of this thesis, is marked by successful rulers whoadopted favorable policies towards their neighbouring states and as such, were able tomaintain the state’s existence consistently until 1391. After this era, due to theinefficient rulers ascending the throne and mismanagement of the state, Nasrid Statecame under Christian rule in 1492 with the marriage of Queen Elizabeth of Castile and Ferdinand King of Aragon, and the political presence of Muslims in this regionwas eradicated.In this context, the thesis focuses on the political, military, and culturalproperties of the period of Mohammad V al-Ghani Billah, which was the last brilliantera in the period of regression of the Andalusian civilization, and thus can be regardedas one of the main constituents in the historical process of Spain.
Keywords: Endülüs; Gırnata; Granada; History; Iberian Peninsula; Islam; İber yarımadası Andalusia; İslam; Middle ages; Nasrids; Nasrîler; Ortaçağ; Tarih